Facile Access to Challenging ortho‐Terphenyls via Merging Two Multi‐Step Domino Reactions in One‐Pot: A Joint Experimental/Theoretical Study. Issue 16 (26th July 2019) - Grau, Benedikt W.; Bönisch, Simon; Neuhauser, Alexander; Hampel, Frank; Görling, Andreas; Tsogoeva, Svetlana B.
Abstract: ortho ‐Terphenyls are of high interest for medicinal chemistry and materials science, but they are difficult to access. Herein, we demonstrate a straightforward and sustainable synthesis of highly functionalized ortho ‐terphenyls via joining an organocatalyzed two‐step domino reaction (Knoevenagel/vinylogous Michael) with a DABCO/CuBr2 co‐catalyzed three‐step domino reaction (cyclization/tautomerization/aromatization) in a one‐pot process. Overcoming necessity to isolate intermediate products leads to a reduction of energy, costs and waste for a broad scope of reactions. DFT calculations have been performed to investigate the thermodynamics of this one‐pot process towards ortho ‐terphenyls and to study the reaction profile of the vinylogous Michael reaction under inclusion of solvent effects. Role of London dispersion forces in this transformation has been elucidated. It is shown that reaction kinetics and thermodynamics are slightly influenced by dispersion interactions. Furthermore, the addition of dispersion energy donors leads to small changes of reaction energies in some cases. Abstract : Two steps, three steps : A straightforward synthesis of difficult to access ortho ‐terphenyls via joining two‐step and three‐step domino reactions in a one‐pot process, is presented. Overcoming necessity to isolate intermediate products leads to a reduction of energy, costs and waste for a broad scope of reactions. DFT calculations have been performed to investigate this facile five‐step one‐pot process.